Multidimension Analysis of the Prognostic Value, Immune Regulatory Function, and ceRNA Network of LY6E in Individuals with Colorectal Cancer - Ting Li; Weidong Liu; Chun Wang; Man Wang; Wenjia Hui; Jiajie Lu; Feng Gao (Journal of Immunology Research)
Background. Lymphocyte antigen 6 complex, locus E (LY6E) is abnormally expressed in several cancers and is associated with poor outcomes. However, the biological role of LY6E in colorectal cancer (CRC) remains largely unknown. Hence, we aimed to evaluate the expression levels, prognostic value, biological functions, and immune effects of LY6E via pan-cancer and CRC analyses using multiple databases. Methods. We analyzed the expression pattern of LY6E in various cancers. The prognostic value of LY6E expression was identified using the Kaplan–Meier analysis and the Cox regression models. We used gene set enrichment analysis (GSEA) to identify the potential functions of LY6E. Correlations between the LY6E expression and various factors, including LY6E methylation level, copy number variation (CNV), microsatellite instability (MSI), and immune checkpoint genes, were also analyzed. The levels of LY6E expression and immune infiltration were analyzed using CIBERSORT. We constructed a regulatory network that was in compliance with the competing endogenous RNA (ceRNA) hypothesis. A ceRNA expression-based nomogram was established. Real-time PCR (qRT-PCR) was applied to validate the expression of LY6E-related ceRNA in CRC cell lines. Results. LY6E is overexpressed in several tumor types, including CRC, and patients with high expression levels of LY6E have a poor prognosis. The Kaplan–Meier analysis and Cox regression analysis showed that LY6E could be considered a favorable prognostic factor in TCGA and GEO cohort. The results of GSEA showed that high LY6E expression levels were associated with immune-related pathways, such as those involved in antigen processing and presentation and the intestinal immune network for IgA production. Six methylation sites of LY6E that were associated with prognostic survival were screened. Moreover, the high levels of LY6E expression were correlated with copy number gain, microsatellite instability high, and immunotherapy response. The results of CIBERSORT analysis demonstrated that the LY6E expression levels were correlated with the infiltration of multiple immune cells, especially T cells. Then, we constructed a ceRNA network (LINC00963/miR-92a-3p/LY6E) and validated it using qRT-PCR. A predictive ceRNA-based nomogram was established and validated. Conclusion. The oncogenic LY6E may serve as a promising marker for the diagnosis and treatment of CRC.